Preliminary study on health effects and their relation to volcanic gas emissions exposure. A case study of two active volcanoes in Costa Rica - Ortiz Apuy, Erick (2022)
[Objective] The objective of this research was to carry out a preliminary diagnosis of the relationship between volcanic gaseous emissions and health effects present among workers of the National System of Conservation Areas (SINAC) of the Poás and Turrialba volcanoes of Costa Rica. [Methodology] Ambient air quality was measured by the presence of gaseous emissions (SO2(g), H2S(g), HCl(g), HNO3(ac) and HF(g)), with sampling carried out in 7 strategic points during 7 months. Analyses were performed using different analytical techniques (ion chromatography, spectrophotometry, portable meters). At the same time, interviews were conducted with a sample consisting of 16 park rangers from the study sites, and their medical records were analyzed to detect a preliminary relationship between exposure to gaseous emissions and reported pathologies. [Results] The principal results (pollutants above the detection limit) reported for the two national parks indicated that the highest value in this study was that of SO2 (average of 3 h) in the Poás Volcano (1.90 ± 0.11) mg/m3. The highest concentration of SO2 in Turrialba was (0.40 ± 0.04) mg/m3 during the same period. During the evaluation of park rangers’ health, it was found that the most frequently reported pathologies that impact health in the study population were irritation of the mucous membranes-eyes (n = 9), headaches (n = 8), and fatigue (n = 8). [Conclusion] The results obtained for the gaseous emissions and their possible relationship with pathologies and medical records indicated by park rangers provide a baseline for future research on the subject. A greater number of measurements over longer periods of time is recommended. At the same time, it is necessary to use surveys and carry out medical controls that include tests on specimens such as blood, urine, hair, and saliva, as well as the use of biological and chemical indicators that allow a pathology to be more directly related to a specific chemical contaminant.